Religious Entrepreneurs' Motives and Practices in the Different Phases of the Entrepreneurial Process - Kojana, Tholoana; Mamabolo, Anastacia (Senate Hall, 2020)
Religion is argued to contribute to entrepreneurship; however, there is scant research that explores its role in the different phases of the entrepreneurial process. Therefore, the purpose of this study is to explore the religious motives and practices of religious entrepreneurs during the different phases of the entrepreneurial process, including the formation of entrepreneurial intentions, opportunity search/identification, evaluation, and exploitation. The analysis is based on the data gathered from in-depth interviews conducted with 12 established charismatic Christian and Jewish entrepreneurs who operate in various business sectors in South Africa. The results show that entrepreneurs' motives for incorporating religious beliefs into their business ventures include sense-making, human capital endowments, access to networks and trust-based relationships, access to ethical business activities, and dealing with challenges in the entrepreneurial process. These motives are supported by religious practices such as prayer, reading of Holy Scriptures, church or synagogue attendance, and thanksgiving activities. Our findings show that the significance of religious motives and practices differs across the entrepreneurial phases. The results also show that religious beliefs, motives and practices differ across the various religions and should not be generalized to other religions and contexts or countries. The study concludes with implications for future research.
Keywords: entrepreneurial process|religious motives|religious practices|religion|emerging market|South Africa